A long way to paradise a new history of British Columbia politics - McDonald, Robert A. J. 1944- (UBC Press, 2021)
"Polarized. Partisan. The political landscape of British Columbia has been characterized by divisiveness since Confederation. But why and how did it become Canada's most fractious province? A Long Way to Paradise traces the evolution of political ideas in the province from 1871 to 1972, exploring British Columbia's journey to socio-political maturity. Robert McDonald explains its classic left-right divide as a product of "common sense" liberalism that also shaped how British Columbians met the demands and challenges of a modernizing world. This lively, richly detailed overview provides fresh insight into the fascinating story of provincial politics in Canada's lotus land."--
Keywords: Geschichte 1871-1972; Politik; Politisches Denken; British Columbia; British Columbia / Politics and government; British Columbia / Politics and government / 1871-; Politics and government